Morphological Versatility in the Self-Assembly of Val-Ala and Ala-Val Dipeptides - Erdogan, Hakan (Langmuir : the ACS journal of surfaces and colloids, 2015)
Since the discovery of dipeptide self-assembly, diphenylalanine (Phe-Phe)-based dipeptides have been widely investigated in a variety of fields. Although various supramolecular Phe-Phe-based structures including tubes, vesicles, fibrils, sheets, necklaces, flakes, ribbons, and wires have been demonstrated by manipulating the external physical or chemical conditions applied, studies of the morphological diversity of dipeptides other than Phe-Phe are still required to understand both how these small molecules respond to external conditions such as the type of solvent and how the peptide sequence affects self-assembly and the corresponding molecular structures. In this work, we investigated the self-assembly of valine-alanine (Val-Ala) and alanine-valine (Ala-Val) dipeptides by varying the solvent medium. It was observed that Val-Ala dipeptide molecules may generate unique self-assembly-based morphologies in response to the solvent medium used. Interestingly, when Ala-Val dipeptides were utilized as a peptide source instead of Val-Ala, we observed distinct differences in the final dipeptide structures. We believe that such manipulation may not only provide us with a better understanding of the fundamentals of the dipeptide self-assembly process but also may enable us to generate novel peptide-based materials for various applications